Upper-Level Winds over Southern Ontario: O-QNet Wind Profiler and NARR Comparisons. Issue 1 (1st January 2017) - Taylor, Peter A.; Weng, Wensong; Wang, Zheng Qi; Corkum, Mathew; Malik, Khalid; Sharma, Shama; Hocking, Wayne
ABSTRACT: Upper-level winds are primarily measured by tracking the position of radiosonde balloons as they rise through the atmosphere. Radiosondes are released from a global network at 0000utc and 1200utc each day, and data are quickly available to the world's weather services, as well as to the public. The network is relatively coarse spatially, and there are normally only two soundings per day. In an endeavour to provide better spatial and temporal upper-level regional wind measurements, the O-QNet (a demonstration very high frequency wind profiler network for Ontario and Quebec) was installed and has been operated by York, Western, and McGill Universities with support from Mardoc Inc., The Weather Network, and Environment and Climate Change Canada. Initial funding was provided by the Canada Foundation for Innovation, the Ontario Innovation Trust, and Mardoc Inc. The present paper reports primarily on comparisons between winds measured by the O-QNet profilers and the winds reported in the North American Regional Reanalysis (NARR). There is good agreement between the two, which provides support for the use of NARR data to investigate longer term variations in upper-level winds associated with climate change for this region.